Masarig climate change-induced architectural response through the redevelopment of Bula Terminal Market - Hong, Sun Alexis Marie U. (College of Architecture, University of the Philippines Diliman, 2022)
In the Philippines, the agriculture sector is critical to both the country's economy and the people's well-being. As of 2018, around 10.9 million Filipinos work in the agriculture industry, accounting for 26% of national employment and contributing to approximately 10% of the Philippines' gross domestic product (GDP) (Midna, 2014). In addition, scholars have recognized the important role of the agriculture sector in increasing food availability and attaining food security. However, the worsening conditions brought about by climate change have disrupted food production in agricultural areas including Bula, Camarines Sur. Bula's inherent vulnerability to climate change-induced shocks, such as drought and flooding, is proven to be one of the causes of loss of livelihood, food insecurity, and low crop yield in the municipality (Food and Agriculture Organization of the United Nations, n.d.). Although farmers and fisherfolk have developed coping mechanisms -- early planting, bamboo craft making, and utilizing alternative staples--, these have not brought significant change to their conditions due to the underlying issues of poor road networks and a lack of marketing support. The thesis project aims to address the issue of the ineffectiveness of Bula's current marketing system in supporting the coping mechanisms of the agricultural sector of Bula with special attention to economic development, community involvement, and connectivity. The project will be looking into literature and precedents on food hubs, public markets, and transportation infrastructure in order to discover strategies that would help the community manage the effects of climate change. This will lead to the redevelopment of a Public Terminal Market devoted to enhancing economic capacity, promoting citizen engagement, and improving accessibility for the purpose of establishing a more effective defense mechanism against the threats of climate change in the agriculture sector of Bula, Camarines Sur.